ISLAM DAN PRODUK HALAL: MUSLIMAH, KOMODIFIKASI AGAMA DAN KONSOLIDASI IDENTITAS KEAGAMAAN DI INDONESIA - Suhadi, Muhammad; Muslim, Azis (Profetika: Jurnal Studi Islam, 2022)
This article discusses Islam and Halal products. Specifically, this article highlights a number of commercial advertisements for halal products that use religious norms as branding in Indonesia. The advertisement is seen as a commodification of religion and consolidation of religious identity, as well as showing the lifestyle of middle class Muslims. This article also explores the perceptions of young rural Muslim women who are members of the Parit Baru Village Mosque Youth Association regarding Islamic phenomena and halal products. Methodologically, this article is a descriptive qualitative research. The data in this study were obtained from the field through direct interviews with a number of Muslim women at the Parit Baru Village Mosque, and also from searching data through various literatures, books, magazines and data available on the internet related to this research. The results of the study show that Islam is a broad religion, marked by Islamic attention and regulations regarding halal products for consumption by Muslims in their daily lives. This article also concludes that advertisements for halal products in Indonesia use religious norms as branding to gain profit on the one hand, and indirectly educate middle class Muslims, especially women, to maintain the use of the hijab as a form of representation of religious identity on the other hand. This can be seen as a form of consolidation of religious identity on the one hand and the commodification of religion on the other.Artikel ini membahas tentang Islam dan produk Halal. Secara spesifik, artikel ini menyoroti sejumlah iklan komersial produk halal yang menggunakan norma agama sebagai branding di Indonesia. Iklan tersebut dilihat sebagai sebuah komodifikasi agama dan konsolidasi identitas keagamaan, serta menampilkan gaya hidup Muslim kelas menengah. Artikel ini juga menelusuri persepsi anak muda muslimah pedesaan yang tergabung dalam Ikatan Remaja Masjid Desa Parit Baru terkait fenomena Islam dan produk halal. Secara metodologi, artikel ini merupakan penelitian kualitatif deskriptif. Data dalam penelitian ini diperoleh dari lapangan melalui wawancara langsung dengan sejumlah Muslimah Remaja Masjid Desa Parit Baru, dan juga berasal dari penelusuran data melalui berbagai literatur, buku-buku, majalah dan data-data yang tersedia di internet yang berhubungan dengan penelitian ini. Hasil studi menunjukkan bahwa Islam adalah agama yang luas, ditandai dengan perhatian dan peraturan Islam terkait produk halal untuk dikonsumsi kalangan Muslim dalam kesehariannya. Artikel ini juga menyimpulkan bahwa iklan-iklan produk halal di Indonesia menggunakan norma agama sebagai branding untuk mendapatkan keuntungan disatu sisi, dan secara tidak langsung mengedukasi Muslim kelas menengah khususnya perempuan untuk tetap mempertahankan penggunaan jilbab sebagai bentuk representasi identitas keagamaan di sisi lain. Hal ini dapat dipandang sebagai bentuk konsolidasi identitas keagamaan disatu sisi dan komodifikasi agama di sisi lain.